Sport jako perspektivní potenciál rozvoje zaměstnanosti v EU [Sport as a prospective potentional for employment in the EU states] - Tomáš Dohnal; Vladimír Hobza (Palacký University Olomouc, 2008)
Zaměstnanost a ekonomický růst jsou dvěma nejdůležitějšími cíli, sledovanými v rámci Lisabonské strategie, pomocí níž by se z Evropy v dalších letech měl stát celosvětově nejdynamičtější a nejkonkurenceschopnější ekonomický region. Vlády jednotlivých zemí doposud plně nerozpoznaly prorůstový a zaměstnanostní potenciál, který skrývají dopady sportu a průmyslu volného času. Jejich vyhodnocení je velmi složité a přesto, že byly mnohé analýzy ve vyspělých zemích světa publikovány, jejich praktické využití je teprve na počátku. Prostřednictvím vybraných oblastí jsou dokumentovány případové studie potenciálního rozvoje zaměstnanosti iniciované rozvojem sportu. Možný vliv na potenciál zaměstnanosti a uplatnění na trhu práce se také staly jedním z významných faktorů tvorby nových curricul oboru rekreologie, které jsou zpracovávány v souvislosti s projektem Evropských sociálních fondů. [Employment and economic growth are monitored as two of the most important goals within the Lisbon strategy, which should make Europe the world's most dynamic and competitive region in the coming years. Governments of member states have not yet fully recognized the growth and employment potential of sport and leisure time industry. The valuation is very complicated and even though some analyses were already published in developed countries, the practical use is at the beginning. Case studies prove potential growth of employment in selected fields initiated by development of sport and leisure time industry. These fields include tourism, production and selling of sport equipment, services (physical condition), sport events, professional sport, media etc. The Czech Republic has an employment in sport of 0,3% which is just and average within the EU. Europe will need around 800 000 to 1 million professional experts for sport and leisure time. Considering this, all related fields of study in sport and free time management are very perspective. In the current dynamic environment, it is necessary to look closer to fields that were not yet fully used for employment and to establish new professions for fulfilling new needs, which will have an additional effect on employment. Therefore the employment potential with asserting oneself on the labour market has become one of significant factors in creating new curricula in recreology. The new curricula are prepared in connection with the project of European social funds.]